Out of combat and into the classroom: how combat experiences affect combat veteran students in adult learning environments - Clark, Maria L. (Kansas State University, 2014)
A new group of learners is emerging in the adult learning environment as a result of the United States being at war for more than 10 years. More than two million warriors served in the Global War on Terrorism (GWOT). Educational institutions across the United States are experiencing growing numbers of students who are military combat veterans of the GWOT. These numbers will continue to grow as more of them transition back into life after combat. These students are arriving in class with varying levels of combat trauma experience and possibly Post Traumatic Stress Disorder (PTSD), major depression, Traumatic Brain Injury (TBI) or a combination of these and other difficulties. The purpose of this research was to learn from military veteran students how their combat experience affects them in the classroom. Specifically it looked at the types of combat experiences they have and the types of physical and mental effects they report experiencing while attending and participating in educational learning activities. This research h sought to gain insight into how combat experience influences the learning experience for GWOT military combat veterans who participate in an educational learning environment. It explored the types of experiences these students bring into that learning environment and how their participation in learning activities is affected.
Keywords: Veterans in college; Adult education learning environment; Military education; Combat stress effects on learning; Effects of combat and trauma; Global War on terrorism combat veterans; Adult Education (0516); Continuing education (0651); Military Studies (0750)